Measuring Perceived Internal Marketing and Employee Engagement in Higher Education Institutions - Kyriacou, Evdoxia; Zarkada, Anna K. (My University, 2023)
Despite the longevity and popularity of the Internal marketing (IM) in the service literature, its structure is yet unclear (Ballantyne, 2003; Huang & Rundle-Thiele, 2015; Qaisar & Muhamad, 2021; Tsai & Tang, 2008). The literature on Employee Engagement (EE) explains the employees’ emotional commitment and their psychological presence in their job and organization, but it lacks of a concurrence regarding its definition and its measurement (Kossyva et al., 2022). Despite the importance and dynamism of the Higher Education (HE) sector, there is only scant research data of IM and EE in HEIs (Tsarakhova & Kabanov, 2020; Vel et al., 2019; Vieira-dos Santos & Gonçalves, 2018; Yildiz & Kara, 2017). The aim of this paper is to explore the structure and components of IM and EE in HEIs. A two-stage mixed methods design was adopted, comprising 15 semi-structured interviews with a convenience sample of employees of a public HEI and a census of all employees in public and private HEIs in Cyprus.
Keywords: Internal marketing; Employee Engagement; Higher Education